Karaim literature as a source of information on the spoken language. A case study of the early 20th-century Lutsk Karaim dialect - Németh, Michał (Karaite Archives, 2013)
The present article presents an analysis of a Lutsk Karaim literary work, namely Sergiusz Rudkowski’s Dostłar, which was published in two parts in 1931 and 1939. The two characters of the drama use colloquial language and therefore the work appears to be until now the only source of knowledge on Lutsk Karaim in its spoken form. The linguistic peculiarities of the drama are compared with other non-literary sources that reflect everyday language used at the turn of the 19th and 20th centuries. The present study has been carried out in order to determine whether the language of the drama was caricatured by the author, and thus exaggerated to some extent, or whether it reflects the factual command of Karaim during that period. In the final analysis, it is safe to say that the drama’s language should be treated as a reliable source of knowledge. It is important to note that it contains linguistic elements (swearwords, abusive words, Hebrew elements, &c.) that are absent from all other colloquial linguistic materials.